2018
DOI: 10.3390/en11030518
|View full text |Cite
|
Sign up to set email alerts
|

Closing the Energy Efficiency Gap—A Systematic Review of Empirical Articles on Drivers to Energy Efficiency in Manufacturing Firms

Abstract: Abstract:Research has identified an extensive potential for energy efficiency within the manufacturing sector, which is responsible for a substantial share of global energy consumption and greenhouse gas emissions. The purpose of this study is to enhance the knowledge of vital drivers for energy efficiency in this sector by providing a critical and systematic review of the empirical literature on drivers to energy efficiency in manufacturing firms at the firm level. The systematic literature review (SLR) is ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
75
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(78 citation statements)
references
References 98 publications
(258 reference statements)
3
75
0
Order By: Relevance
“…and "Organizational" (Divergent interests and Low status of energy efficiency). Their manifestation largely determines an insufficiently high level of interest of company's management in the field of energy saving and energy efficiency measures implementation [49,91]. In the approach developed, we showed that the interest of top management in the problems of energy saving and energy efficiency will increase as their importance grows from the standpoint of the company's strategic goals achievement.…”
Section: Characteristics Of Energy Saving and Energy Efficiency Positmentioning
confidence: 96%
See 1 more Smart Citation
“…and "Organizational" (Divergent interests and Low status of energy efficiency). Their manifestation largely determines an insufficiently high level of interest of company's management in the field of energy saving and energy efficiency measures implementation [49,91]. In the approach developed, we showed that the interest of top management in the problems of energy saving and energy efficiency will increase as their importance grows from the standpoint of the company's strategic goals achievement.…”
Section: Characteristics Of Energy Saving and Energy Efficiency Positmentioning
confidence: 96%
“…Consequently, they identified a framework of factors influencing successful achievement of energy efficiency, including the size of the company, solution of environmental problems, implementation of organizational innovations, etc. [48,49]. The outcomes obtained by researchers from different countries suggest two characteristic features of competitive companies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…worldwide manufacturing industries' energy-saving potential is estimated to be 20% through 2050 [6]. Therefore, energy efficiency improvement of the manufacturing industry is identified as an important path for energy savings and climate change mitigation [1].…”
Section: Figurementioning
confidence: 99%
“…Nowadays, climate change has become one of the most imperative topics [1]. Manufacturing processes are partially responsible for climate change due to the emissions generated as a result of energy consumption [2].…”
Section: Introductionmentioning
confidence: 99%
“…awareness, image, management system, energy strategy, energy audits and KPIs, management ambition and support) and structure (e.g. organisational structure, cooperation between units), have, in a recent literature review, been identified as playing a vital role for improving energy efficiency (Solnørdal and Foss, 2018) along with knowledge-related drivers and the importance of having well-functioning relations within the organisation and a committed top management (Lawrence et al, 2019).…”
mentioning
confidence: 99%